The Effect Of Brand Image And Modeling Of Vicarious On Bandwagon Effect, Snob Effect And Veblen Effect - Adnan, Adnan (JOURNAL OF ECONOMIC SCIENCE, 2015)
This study aims to discuss the extent of brand image which may affect the interest of consumers to the brands which are the spearhead of the company and is also a reflection of the overall quality within the company. Brand image of a product causes the consumers in associating and buying it, so that the consumers will directly pay dearly to get a product with a particular brand. Brand image also has a very important role in loyalty to the brand, because if it has a bad image, of course it will reduce the consumers confidence in buying. The impression of brand image can be enhanced through Vicarious modeling that can be used as an approach to developing a marketing strategy as a reference for someone to change his behavior through observation of vicarious modeling as a real modeling (overt modeling) which is based on the use of modeling to help others in gaining a new feedback for development of an effective market.Brand image and vicarious modeling have an impact on the Bandwagon effect which is a behavior or act of buying a product because of an encouragement / influence from the other consumers (bandwagon effect), and it usually has a positive correlation with the "bandwagon effect. Likewise with the Snob Effect which is the effect of the purchase and prestige due to the effects of prestige that will increase the demand for the goods when the price rises, because the increase or the high price of goods will only be able to be paid by consumers who indicate their economic status in society. In Veblen Effect someone consumes the good to get the status of his environment, so that every consumer will always increase the consumption for showing off.